Uji Aktivitas Antijamur Ekstrak Daun Sungkai terhadap Candida albicans dan Malassezia furfur - Maryam Jamila Arief; Aninda Dewi Meilisari (Pusat riset dan Inovasi Nasional, 2025)
Fungal infection is an infectious disease that has a fairly high prevalence in tropical countries. Fungi that cause infections include Candida albicans and Malassezia furfur. Sungkai plants (Peronema canescens) can be used as antifungals because they contain secondary metabolite compunds, such as flavonoids, tannins, and saponins. The pupose of this study was to determine the antifungal activities of 96% ethanol extract of sungkai leaves against Candida albicans and Malassezia furfur. The antifungal activity test of the extract used the disc diffusion method with test solution concentrations of 6.25%, 12.5%, 25%, and 50% with ketoconazole as positive control and sterile aquadest as a negative control. The best inhibition results were obtained at a concentration of 50% with an average inhibition zone of 9.8mm (moderate category) against Candida albicans and an average inhibition zone of 6.88mm (moderate category) against Malassezia furfur. This shows that ethanol extract of sungkai leaves has antifungal activities.